Students’ virtual learning styles in an online context - Goulão, Fátima (2013)
The objectives of our research were, on the one hand, to identify students’ profiles that use virtual space in the online context and on the other hand, to verify if there were differences in those profiles, in terms of gender. Data collection was made through a questionnaire composed of 3 parts. The first concerned the identification of the sample. The second part contained questions to characterize the use made of the Internet. Finally, to identify the users’ profile of virtual learning space we applied the questionnaire of Style usage of Virtual Space which is composed by a set of 40 statements. Each subject should select those that best fit their situation. The questionnaire refers to 4 different styles. The collection of information was carried out online and the questionnaires were anonymous. The sample was a total of 62 distance-learning students. In terms of gender, 26% were male and 74% female. The average age is 38 years old. There were identified 4 styles of virtual learning space usage were identified and the results point out to the predominance of one of the styles – type A -, called participatory use style in virtual space. With regard to gender it was found a similar behaviour in men and women, not having been found significant differences. Knowing virtual learning space users’ profile is very relevant to help us understand the learning processes in these contexts. Furthermore, this knowledge provides us with the information required to structure the pedagogic context and the appropriateness of teaching methodologies.